The mediating role of emotions in offline and online political participation: A post-social outbreak study in Ecuador and Chile - Villagrán, Loreto; Reyes-Valenzuela, Carlos; Alzugaray, Carolina; Zumárraga-Espinosa, Marcos; Méndez, Jaime (Frontiers in Psychology, 2023)
Introduction In 2019, there was a period of social outbreaks in several Latin American countries, which share a background of social inequality, distrust in authorities, a crisis of representativeness, and discontent towards social and economic policies. In October 2019, in Ecuador and Chile, participation in these protests was characterized by street protests and broad political participation in social networks and alternative media, which were followed or interrupted by the COVID-19 pandemic. These facts have been deeply researched, addressing causal and structural factors of the phenomenon, the alternatives of political participation, and the role of emotions as determinants of action in these contexts. The objective of this study is to explore offline and online political participation (Facebook) after the social outbreak of 2019 in both countries, based on political interest, and how emotions intervene, especially negative ones, in a context of high demobilization. Methods A descriptive, correlational ex post facto and cross-sectional methodology was used, with the participation of 367 people, 210 from Ecuador (57.2%) and 157 from Chile (42.8%), aged between 17 and 48 years (M = 22.13, SD = 3.73). The measurement was carried out from 2020 to 2021. Results A mediation analysis showed that people who are more interested in politics are more likely to experience anger and anxiety with the political and economic situation, which motivates conventional political participation (Model 1). In Model 2 people who showed greater concern about the political and economic impacts of the COVID-19 pandemic and together with anger, favor online political participation, especially local support. Discussion These results suggest the influence of emotions on political participation, which occurs when there is an increase in social discontent due to government policies adopted during the pandemic and which represents a continuity of the discontent that was expressed in the October 2019 social outbreak.